Pre-collision safety risk assessment using multi-body simulation / Eko Deprianto - Eko , Deprianto (2021)
Road accident has become an alarming phenomenon across the country. Its negative impact does not only include loss of lives but also affects the economy. Hence, road safety assessment has become a crucial preventive measure. Several assessment studies have been developed and implemented. However, they are mostly conducted in the post-accident level, in which the accident has already taken place. A study using a vehicle dynamic simulation is then proposed to assess the accident at the post-accident level. In order to check its effectiveness, two accident-prone locations were chosen, its road segments are then generated into a simulated environment. Several combinations of the simulation parameters are then introduced to the simulation, such as road geometries, road profile, road condition, vehicle type, and driving characteristic. The outcome is then analyzed through visual observation and data analysis. Based on the study conducted, the crash report data obtained from the accident-prone location has almost similar output when the simulation parameter input matched with the crash data. An apparent visual indication, such as a vehicle crashing event, can also be seen from the simulation result. The vehicle dynamic data gives promising results by showing prediction in the form of an erratic response before failing. The vehicle dynamic response parameters are, namely, roll and lateral acceleration. It is concluded that this road safety assessment method can successfully replicate the actual type of accident that happens in the accident-prone location. Translating the actual road profile into a simulation form can be considered successful since it can imitate the particular road profile. The vehicle responses of roll and lateral acceleration can be used as a safety assessment key indicator in identifying the point of failure of a road stretch. Implementing similar methods to other road segments will result in the ability to find the dangerous combination of parameters used as a countermeasure for the particular road segment.